The use of “Acellbia” – a biosimilar of rituximab in systemic sclerosis - L. P. Ananyeva; L. A. Garzanova; O. V. Desinova; R. U. Shayakhmetova; M. N. Starovoytova; O. A. Koneva; O. B. Ovsyannikova; S. I. Glukhova; E. L. Nasonov (Научно-практическая ревматология, 2023)
Introduction. The possibilities of modern therapy for systemic sclerosis (SSc) remains limited, since most of the used drugs do not have a diseasemodifying effect. This encourages the study of new approaches that potentially affect the fundamental pathological processes underlying the disease. One example is anti-B cell therapy, in particular rituximab (RTX). Until now RTX do not have a registration for the treatment of SSc, but there is a large positive experience of its use, which is reflected in recent meta-analyses and clinical recommendations. Complicated and expensive methods for obtaining genetically engineered biological preparations have contributed to the emergence of more accessible biosimilars, one of which is the RTX biosimilar, Acellbia (Biocad, Russian Federation). The “biosimilar” versions of RTX might reduce the cost of therapy and increase patients accessibility to this treatment option. The RTX biosimilar Acellbia (ACB) has received approval in Russian Federation in 2014 for all indications held by reference RTX (including rheumatoid arthritis and ANCA-associated vasculitis).The aim of this study was to investigate the efficacy and safety of Acellbia in patients with systemic sclerosis.Material and methods. Our prospective uncontrolled study included 20 patients (14 women) aged 50±14 years, with a disease duration of 3.5±2.7 years. Indications for the prescribing of ACB were high disease activity and the presence of risk factors for progression. All patients had radiological signs of interstitial lung disease, 13 (65%) were positive for antibodies to topoisomerase 1. None of the patients had previously been treated with biological therapy. All patients received glucocorticoids in low doses and 15 (75%) patients were not on concomitant immunosuppressants during the study. ACB was administered in doses of 2 g (two doses of 1 g with a weekly interval) at inclusion of the study and after 6–8 months according to the same scheme, cumulative dose – 4 g. An assessment of basic measurements was obtained at baseline (Point 0), before the second course (after 7.2±1.7 mo, Point 1) and at the end of follow-up (13.4±1.6 mo, Point 2). The results are presented in the form of mean values and standard deviations.Results. There was a positive effect on the main manifestations of the disease, which accompanied by stable depletion of CD19+ B lymphocytes in the peripheral blood. At the intermediate assessment (between points 0–1), no significant changes were observed, with the exception of the skin score. At the end of the study, most of the parameters showed a significant improvement between points 0–2. The activity of the disease (EScSG-AI) decreased, and the skin score decreased from 12.8±11 to 6.2±5.6 (p=0.002). The forced vital capacity (% of predicted) increased from 89±18.2 to 98.26±16.13% (p=0.0002), and the diffusion capacity of the lungs (% of predicted) increased from 56.8±15.7 to 61.9±17.2% (p<0.019). A significant decrease in CRP, antitopoisomerase-1 antibodies, as well as IgG (from 12.6±2.6 to 10.2±2.2 g/l) was noted. Repopulation to normal level of B lymphocytes did not occur in any case, and complete depletion of B lymphocytes at the end of the study was maintained in 83% of patients (15 of 18). The quality of life questionnaire SHAQ improved (p=0.0001), and the average dose of prednisolone was reduced from 11.0±2.7 to 9.4±2.3 mg/day (p=0.03). Positive changes according to HRCT was evident in 9 (45%) patients due to a decrease in ground glass opacity. The frequency and spectrum of adverse events (AEs) corresponded to those already known for RTX. Of the 20 patients who received 2 courses of ACB, two withdrew from the evaluation at Point 2 due to pregnancy (1) and lung cancer (1). A total of 11 (55%) AEs were reported in 9 (45%) patients, most of them were classified as mild. Infectious complications developed in 7 (35%) patients: respiratory infections of the upper respiratory tract (4), positivity in the TB skin test (2), otitis (1), cystitis (1) and cholecystitis (1). One patient developed calf vein thrombosis and lung cancer was diagnosed in one case.Conclusion. Our data suggest that Acellbia could be used for the treatment of SSc. A short-term, prospective, uncontrolled study showed good efficacy and acceptable safety of the ACB biosimilar in SSc. A significant decrease of skin fibrosis and improvement of lung functions have been proven. The clinical effect of ACB manifested by the 6th month from the start of therapy and reached its maximum one year after its initiation. Due to the positive efficacy of ACB, it can be prescribed for the patients with SSc with ineffectiveness and/or intolerance to immunosuppressants, and could be considered as a first-line therapy. Our data should be confirmed by the results of controlled clinical trials.